Shape optimisation of rim structure of aluminium alloy car wheels based on 90° impact test - Guangdong Zhang; Shike Tao; Yangyang Zhou; Zhen Ye; Jianjun Lu; Risheng Li; Shihui Li; Linzhen Zhou; Tong Deng (Scientific Reports)
Abstract Automotive wheels are critical components for vehicular safety, with the rim subjected primarily to radial bending loads during operation. Balancing rim thickness and structural integrity under these loading conditions is imperative. This paper develops and validates an innovative shape optimisation approach utilising the 90° wheel impact test methodology. A simplified 2D finite element model was formulated for rim optimisation to address the computational inefficiency of conventional 3D simulation-based optimisation in product development while exploiting rim geometry’s rotational symmetry. The design of experiments technique was employed to identify key stiffness-influencing factors and their interactions. Subsequent shape optimisation, guided by analytical insights, yielded an engineered rim configuration. Comparative 3D simulations of 90° impact performance demonstrated a 0.51 mm reduction in inner rim flange deformation alongside a 59 g mass reduction, achieving dual objectives of enhanced structural performance and lightweighting. This streamlined optimisation methodology significantly enhances development efficiency while providing engineers with critical insights into parametric influences on rim strength characteristics.